2013
DOI: 10.4314/sokjvs.v11i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of parasitic infections of stray cats in Jammu, India

Abstract: Stray cats are afflicted with various parasitic infestations and the infective stages of these parasites may spread infection to other animals including human beings. The study was conducted for a period of one year from March 2009 to February 2010 to determine the prevalence of parasitic infection in and around Jammu-humid subtropical zone of North Western India. A total of 100 stray cats were examined using standard parasitological methods. Post mortem examinations of stray cats were also conducted to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
3
5
0
Order By: Relevance
“…In the present study, 23.72% (121/510) of canine faecal samples were positive by conventional microscopic examination, however similar studies conducted by Palmer et al (2008) have also recorded a similar type of overall prevalence of 23.9% in dogs and 18.4% in cats. Roger et al (2004), Katagiri and Oliveira-Sequeira (2008) and Borkataki et al(2013) have recorded higher prevalence as reported in the present study which might be attributed to the sample size, population targeted and species of parasite identified. The species wise distribution results of our study showed that Ancylostoma spp.…”
Section: Resultssupporting
confidence: 43%
“…In the present study, 23.72% (121/510) of canine faecal samples were positive by conventional microscopic examination, however similar studies conducted by Palmer et al (2008) have also recorded a similar type of overall prevalence of 23.9% in dogs and 18.4% in cats. Roger et al (2004), Katagiri and Oliveira-Sequeira (2008) and Borkataki et al(2013) have recorded higher prevalence as reported in the present study which might be attributed to the sample size, population targeted and species of parasite identified. The species wise distribution results of our study showed that Ancylostoma spp.…”
Section: Resultssupporting
confidence: 43%
“…In similar researches conducted on the endoparasites of stray cats in Kashan Cryptosporidium was not pointed out (Arbabi and Hooshyar 2009). Another microscopic study by Borkataki indicated 4 % prevalence of Cryptosporidium among the stray cats in Jammu region in India (Borkataki et al 2013). Investigation about cryptosporidiosis in birds in Iran have been mostly done on the turkey, poultry, ostrich and borealis (Banani et al 2000;Shemshadi et al 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Stray cats are predators that highly susceptible to a variety of parasitic infections because they can go everywhere and become a sources of parasite (Loss et al, 2013;Borkataki et al, 2013). Parasites in cats can impact to their health and to human in the vicinity (Krecek et al, 2010;Subrata et al, 2015), Toxocara sp and Ancylostoma sp are known to cause larva migrans in human being (Overgaauw and Knapen, 2013;Wiwanitkit and Wiwanitkit, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, public health education should be given to the pet owner and general public regarding the hazards of zoonotic diseases. Children are at most serious risk as they have the habit of playing with pet or even from the environment where cat feces may be present (Borkataki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%